2020
DOI: 10.1002/ejp.1606
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in SUMOylation of the hyperpolarization‐activated cyclic nucleotide‐gated ion channel 2 during persistent inflammation

Abstract: Background Unilateral injection of Complete Freund's Adjuvant (CFA) into the intra‐plantar surface of the rodent hindpaw elicits chronic inflammation and hyperalgesia in the ipsilateral hindlimb. Mechanisms contributing to this hyperalgesia may act over multiple time courses and can include changes in ion channel expression and post‐translational SUMOylation. Hyperpolarization‐activated, cyclic nucleotide‐gated (HCN) channels mediate the hyperpolarization‐activated current, I h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…In these cases, the decrease in expression may represent compensation for prolonged nociceptor hyperexcitability, or redistribution of the channels from soma to axon. In other models of inflammatory pain, both I h and HCN2 protein expression increased [ 21 , 28 , 29 , 49–51 , 54 , 55 ]. In most instances, it was not clear if altered expression represented an adjustment to transcription, translation, and/or post-translational modifications that modify channel turnover.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In these cases, the decrease in expression may represent compensation for prolonged nociceptor hyperexcitability, or redistribution of the channels from soma to axon. In other models of inflammatory pain, both I h and HCN2 protein expression increased [ 21 , 28 , 29 , 49–51 , 54 , 55 ]. In most instances, it was not clear if altered expression represented an adjustment to transcription, translation, and/or post-translational modifications that modify channel turnover.…”
Section: Introductionmentioning
confidence: 99%
“…HCN2 expression is enhanced in multiple subcellular compartments leading to mechanical hyperalgesia [ 21 , 28 , 49 , 51 ]. A detailed immunohistochemical examination of somatic HCN2 protein expression in lumbar 5 (L5) DRG neurons that innervate the hindlimb showed that HCN2 immunoreactivity significantly increased on day 1 post-CFA in small and medium neurons relative to control animals that did not receive CFA injections [ 55 ]. HCN2 staining intensity then returned to baseline by day 3, but the number of neurons expressing HCN2 significantly increased [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations